Three dimensional phenomena driven scientific inquiry using interactive learning spaces effects on students' digital creativity and adversity quotient - Pobadora, Jasmin C.
Approaches to teaching play a crucial role in enhancing students' digital creativity and adversity quotient. Science teachers are encouraged to adopt methods that equip students with skills for a more digitized and challenging future, promote science literacy, and foster resilience even during educational emergencies. These objectives inspired the development of the science instruction termed Three-Dimensional Phenomena-Driven Scientific Inquiry Using Interactive Learning Spaces (3PSI). This study specifically examined the effects of 3PSI on students' digital creativity and Adversity Quotient and explored whether digital creativity is a positive predictor of adversity quotient and vice versa.